FEAR OF COVID-19 AND ITS IMPACT ON THE WORK BEHAVIOR OF FRONTLINE EMPLOYEES IN JAKARTA - Netania Emilisa; Egabetha Amirah Yudhaputri; Karina Ganadi; Matthew Aaron (SEAN Institute, 2023)
This study aims to analyze the effect of fear of covid-19 on job burnout and its impact on the Intention to leave frontline employees in Jakarta. The data used are primary, and the sampling method uses a purposive sampling technique by distributing online questionnaires to 270 frontline employees in various sectors as samples. Hypothesis testing techniques use Structural Equation Modelling and previously performed instrument tests using validity and reliability. From the data processing results, frontline employees do not feel the fear of covid-19, frontline employees do not feel bored in doing their work, do not have physical, emotional, and mental fatigue resulting from work situations, and do not have the Intention to leave. Therefore, frontline employees will continue to work for their current company. The results of hypothesis testing in this study indicate that Fear of Covid has a positive effect on Job Burnout and Intention to Leave; job Burnout has a positive effect on Intention to leave; also Fear of Covid has a positive effect on Intention to Leave by being mediated by Job Burnout. The managerial implication that can be conveyed is that all managers from frontline employees must maintain providing better services so that employees can continue to work without fear of covid-19 and do not have job burnout and remain loyal to their respective companies.